Simulation of haddad surge arrester model on a 132kV overhead transmission line for back flashover analysis using Alternative Transient Program (ATP) - Hassan, Mahadi (2015)
Lightning is a major problem in a transmission line system. Lightning which occurs around the world will give a huge effect on electrical transmission system and also on distribution system division. Lightning-strike commonly generated in two different ways. One of the ways is direct strike to a wire shield (tower top) and another way is shielding failure. A direct-strike to the wire shield generates back flashover as a result of voltage on insulator string magnitude is equal or exceeds the critical flashover voltage (CFO). Therefore, the insulation of surge arrester on transmission line is the way to reducing and finally solving the back flashover problem. This study modelled a 132kV overhead transmission line for back flashover pattern by using ATP/EMTP software before and after implement the Haddad Surge Arrester Model. This study also analyzed and compares the performance of Haddad Surge Arrester Model with ABB Surge Arrester when four different magnitude lightning strike current is injected. From this study, it show that the Haddad Surge Arrester Model has archived the target to protect the transmission line system.